Sebuah Potensi Dan Tantangan Kapal Cepat Rudal (KCR) Dalam Operasi Perang Di Era Moderenisasi Militer - Shidqi Divreda Sulaeman; I Nengah Putra A; Imanuel Dindin (CV. AFDIFAL MAJU BERKAH, 2024)
This research presents a in-depth analysis of the history and contribution of Indonesia's Fast Attack Craft (Kapal Cepat Rudal or KCR), focusing on the evolution from the first generation to the sixth generation. As an archipelagic nation with complex maritime defense challenges, Indonesia views KCR as a critical asset in maintaining sovereignty and maritime security. In the context of military modernization, this research aims to understand the impact of KCR on national defense. The applied research method is Systematic Literature Review (SLR), providing a comprehensive analytical framework for relevant literature on the research topic. A total of 80 articles were collected and analyzed, forming a strong foundation to illustrate the transformation of KCR in terms of history, technology, operations, and tactics. The research results indicate that the first-generation KCR, such as the Komar class, played a key role during the confrontation with Malaysia and various military operations. In the second generation, the Ahmad Yani class showed technological advancements and weapon system success in maintaining national security. The third generation, represented by the Fatahillah class, brought significant innovation with the use of MM38 Exocet missiles, enhancing self-defense capabilities. Subsequent generations demonstrated significant development, both in terms of technology and involvement in humanitarian and regional conflict operations. The sixth-generation KCR, recently completed by PT PAL, marks the peak of Indonesia's military modernization with automatic weapons and state-of-the-art technology. However, challenges for the seventh generation and beyond lie in rapid technological developments, increased firepower and precision, operational flexibility, cyber security, environmental sustainability, and human resource management. By understanding and addressing these challenges, it is expected that future generations of KCR can continue to be a strategic element in Indonesia's maritime defense, responding to evolving threats in the era of military modernization.